Scalable Identifier System for Industrial Internet Based on Multi-Identifier Network Architecture - Wang, Yunmin; Li, Hui; Huang, Ting; Zhang, Xinchun; Bai, Yongjie (IEEE internet of things journal, 2023)
Industrial Internet identifiers have the characteristics of heterogeneity, off-site, and foreign ownership. Traditional identifier systems encountered many problems, such as IP address exhaustion or difficulty in addressing and routing, which cannot meet the demands of numerous heterogeneous and interoperable Industrial Internet objects. At the same time, they also face various security risks. In this article, we propose multi-identifier network for Industrial Internet of Things (MIN-IIoT), a universal identifier system named multi-identifier network architecture for Industrial Internet, which supports the coexistence of multiple identifiers, such as identity, content names, services, locations, and IP addresses. MIN-IIoT establishes a unified identifier system and puts forward a series of identifier management methods, including identifier registration, addressing, mutual translation, and route forwarding. In addition, all identifier information is stored in a hierarchical consortium blockchain to ensure that they are authentic and immutable. Identity authentication, Proof of Vote (PoV)-based consensus algorithm, and trusted computing technology effectively protect the security of MIN-IIoT. Meanwhile, MIN-IIoT is convenient for deployment in various complex Industrial field environments. The extensive experiments show that MIN-IIoT has better performance in identifier management of Industrial Internet than traditional methods.